The need to preserve historical 'sources': an actual example - Franzoni F. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The preservation and the spreading of the historical witness of the age-old process that has been taking place on the territory is of the utmost worth. In order to accomplish this target the 'Associazione Irrigazione Est Sesia' in Novara has carried out some projects aiming to supporting a 'water culture'. Water issues linked to a wiser exploitation of available resources and to a sharper evaluation of the needs uttered in other areas of this planet are getting more and more urgent now. This is the time historical thought becomes a deeper qualifying knowledge item to look for possible answers.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)